ACTIVE COMPOUNDS DETECTION IN AQUEOUS EXTRACT OF GANODERMA APPLANATUM LOCAL ISOLATE - Maher R. S.,; A. H. AL-Bayyar, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to investigate active compounds in the aqueous extract of Ganoderma applanatum mycelium. The aqueous extract of fungus mycelium was prepared and some active compounds were detected, including phenols, flavonoids, tannins, alkaloids, glycosides and resins, all of which gave a positive detection. The effective compounds were diagnosed by GC-Mass Chromatography technique, was revealed that there are a number of compounds that can produce mycelium with ability to inhibit microorganisms, inhibit free radicals and prevent oxidation, as well as their effect in reducing cancerous tumors. As for the effective groups, they were diagnosed by FTIR technique.